2006
DOI: 10.1080/00288330.2006.9517450
|View full text |Cite
|
Sign up to set email alerts
|

Macroinvertebrate diet in intertidal seagrass and sandflat communities: A study using C, N, and S stable isotopes

Abstract: Most seagrass community food-web studies using stable isotopes have been carried out in subtidal habitats during one sampling event. We used C, N, and S stable isotopes to characterise the diet of the dominant macroinvertebrates found in intertidal Zostera capricorni and sandflat communities of southern New Zealand in late summer and winter. The range of δ 13 C and δ 34 S values for Z. capricorni was wide (>5‰), which highlights the importance of accounting for spatial and temporal variability in primary produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 68 publications
4
21
0
Order By: Relevance
“…Chlorophyll a was measured to indicate biomass of microphytobenthos (Jones et al 2011), which had been identified as an important food source for A. affinis (Leduc et al 2006). Comparatively higher microphytobenthos biomass may be related to fewer lugworms feeding at the sediment surface, while sediment chlorophyll a measurements may have also been a weak indicator of microphytobenthos production in muddy areas of this inlet (Jones et al 2011) where low permeability causes a reduction in turnover of algal biomass due to decreased light penetration, solute and particle fluxes (Blanchard et al 2001;Billerbeck et al 2007).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Chlorophyll a was measured to indicate biomass of microphytobenthos (Jones et al 2011), which had been identified as an important food source for A. affinis (Leduc et al 2006). Comparatively higher microphytobenthos biomass may be related to fewer lugworms feeding at the sediment surface, while sediment chlorophyll a measurements may have also been a weak indicator of microphytobenthos production in muddy areas of this inlet (Jones et al 2011) where low permeability causes a reduction in turnover of algal biomass due to decreased light penetration, solute and particle fluxes (Blanchard et al 2001;Billerbeck et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The latter two parameters were used to indicate potential food sources for lugworms (i.e. total available organic material in surface and subsurface sediment, and microphytobenthos biomass in surface sediment, respectively; Longbottom 1970; Leduc et al 2006;Jones et al 2011). For sediment granulometry, samples were wet sieved to extract the fines fraction (B 63 mm), dried to constant weight (60 8C, 48 h) and mechanically sieved to obtain grain size fractions (63Á125, 125Á250, 250Á500, 500Á1000 mm; McManus 1988).…”
Section: Study Sites and Field Samplingmentioning
confidence: 99%
See 2 more Smart Citations
“…In southeastern New Zealand, the lugworm Abarenicola affinis (Ashworth 1903) is common in tidal inlets and estuaries, where it co-occurs with the seagrass Zostera muelleri (Irmisch ex Ascherson 1867) in a number of habitats (Wells 1963;Leduc et al 2006;Goerlitz et al 2013). Zostera muelleri is a short-bladed seagrass (5-15 cm blade length), which is common on intertidal flats throughout New Zealand, where it often exhibits a patchy distribution (Turner 2007).…”
Section: Introductionmentioning
confidence: 99%